Origins of high strength and ductility combination in a Guinier-Preston zone containing Mg-Al-Ca-Mn alloy. (1st April 2019) - Bhattacharyya, J.J.; Nakata, T.; Kamado, S.; Agnew, S.R.
Abstract: The excellent strength and ductility combination of a microalloyed Mg-Al-Ca-Mn, in the peak-aged condition, has been reported previously. However, a mechanistic explanation has not been reported. The present work shows that an enhanced strain-rate sensitivity is responsible for this behavior. Increased post-uniform elongation compensates for the decrease in uniform elongation upon aging, resulting in a total elongation comparable to the solutionized material. The thermally activated nature of dislocation interactions with Guinier-Preston (GP) zones are discussed, and the potential for optimizing mechanical properties by engineering the strain-rate sensitivity through microstructural modifications is highlighted. Graphical abstract: Unlabelled Image